Carnivorous Nepenthes x ventrata plants use a naphthoquinone as phytoanticipin against herbivory - Dávila-Lara, Alberto; Rahman-Soad, Asifur; Reichelt, Michael; Mithöfer, Axel (PloS one, 2021)
Carnivorous plants feed on animal prey, mainly insects, to get additional nutrients. This carnivorous syndrome is widely investigated and reported. In contrast, reports on herbivores feeding on carnivorous plants and related defenses of the plants under attack are rare. Here, we studied the interaction of a pitcher plant, Nepenthes x ventrata , with a generalist lepidopteran herbivore, Spodoptera littoralis , using a combination of LC/MS-based chemical analytics, choice and feeding assays. Chemical defenses in N . x ventrata leaves were analyzed upon S . littoralis feeding. A naphthoquinone, plumbagin, was identified in Nepenthes defense against herbivores and as the compound mainly responsible for the finding that S . littoralis larvae gained almost no weight when feeding on Nepenthes leaves. Plumbagin is constitutively present but further 3-fold increased upon long-term (> 1 day) feeding. Moreover, in parallel de novo induced trypsin protease inhibitor (TI) activity was identified. In contrast to TI activity, enhanced plumbagin levels were not phytohormone inducible, not even by defense-related jasmonates although upon herbivory their level increased more than 50-fold in the case of the bioactive jasmonic acid-isoleucine. We conclude that Nepenthes is efficiently protected against insect herbivores by naphthoquinones acting as phytoanticipins, which is supported by additional inducible defenses. The regulation of these defenses remains to be investigated.